Development of Pop-Up Book Media in Science Learning for Elementary School - Rhamdani, Rhamdani; Ramadan, Zaka Hadikusuma (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2024)
This research aims to develop learning media in the form of Pop-Up Book media during offline learning activities. This research is development research and uses the ADDIE model, namely analysis, design, development, implementation, and evaluation. The data sources used in this research are teachers, students, validators, media experts, material experts and language experts. Data collection was carried out through interviews with class IV teachers at SDN 005 Desa Baru, class IV students and needs analysis. The population in this study included teachers and students of class IV SDN 005 Desa Baru. The researcher's sampling technique used a simple random sampling technique. The sample in this study was one teacher and three class IV students. The qualitative data analysis technique was carried out using the needs analysis method in the form of interviews. Meanwhile, for quantitative data analysis using descriptive statistical methods using validation sheets. Data collection techniques used interviews and validation sheets. Based on the research results of material experts with a total of 83%, media experts with a total of 87.26% and language experts with a total of 93.87% and the overall results obtained were 88.03%. It can be concluded that pop-up book media with various styles of material is very valid to be used as learning media material in elementary schools.